2006
DOI: 10.1016/s0022-5347(05)00999-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Changes in Patients With Prostate Cancer During the First 2 Years of Androgen Suppression

Abstract: Bone mineral density decreases during the first 24 months of androgen suppression with the most relevant effect occurring in the first year. Ward's triangle is the axial skeletal site that reflects the major bone mass loss. Because the deleterious impact of long-term androgen suppression on bone mineral density is inversely related to fracture risk and indirectly related to survival in patients with prostate cancer, early diagnosis and prevention of bone mass loss are warranted in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 19 publications
4
58
1
2
Order By: Relevance
“…However, it remains unclear whether ADT has a similar influence on the BMD of East Asian patients with PCa. Although other studies found a high incidence of osteoporosis in western ADT-treated patients with PCa (Bruder et al 2006, Morote et al 2006, we found that this was not true for Japanese patients with PCa, as only 10.8% (4/37) of the ADT-treated patients exhibited osteoporosis. However, ADT did mildly promote osteoporosis in Japanese PCa patients, as even fewer of the hormone-naive PCa patients (2.3%; 1/43) had osteoporosis, although this difference from ADT-treated patients did not quite achieve statistical significance (PZ0.294).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, it remains unclear whether ADT has a similar influence on the BMD of East Asian patients with PCa. Although other studies found a high incidence of osteoporosis in western ADT-treated patients with PCa (Bruder et al 2006, Morote et al 2006, we found that this was not true for Japanese patients with PCa, as only 10.8% (4/37) of the ADT-treated patients exhibited osteoporosis. However, ADT did mildly promote osteoporosis in Japanese PCa patients, as even fewer of the hormone-naive PCa patients (2.3%; 1/43) had osteoporosis, although this difference from ADT-treated patients did not quite achieve statistical significance (PZ0.294).…”
Section: Discussioncontrasting
confidence: 99%
“…The effect of ADT on BMD and its ability to induce osteoporosis in Caucasians and blacks, mainly in western countries, are now well documented (Greenspan et al 2005, Bruder et al 2006, Morote et al 2006. However, it remains unclear whether ADT has a similar influence on the BMD of East Asian patients with PCa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that we did not see changes at the lumbar spine in 6 months due to degenerative changes and the small group. However, changes were significant at the hip and are consistent with previous data in which there was significant bone loss within the first 6 months of ADT [3,4,12]. As in the present study, these investigators did not find significant differences in gastrointestinal symptoms between groups.…”
Section: Discussionsupporting
confidence: 93%